Trait variations and expression profiling of OsPHT1 gene family at the early growth-stages under phosphorus-limited conditions - Anandan, Annamalai; Parameswaran, Chidambaranathan; Mahender, Anumalla; Nayak, Amaresh Kumar; Vellaikumar, Sampthamprajan; Balasubramaniasai, Cayalvizhi; Ali, Jauhar (Springer, 2021)
To better understand the early response of genotypes to limited-phosphorus (P) conditions and the role of the phosphate transporter OsPHT1 gene family in the presence of PSTOL1, it is essential to characterize the level of tolerance in rice under limited-P conditions. In the present experiment, six rice genotypes were studied in three-way interactions [genotype (G) × phosphorus (P) × duration (D)] by comparing them at two instances (14 d and 28 d) under seven different concentrations of P (0.5‒10.0 ppm) in a hydroponic system. Trait differences and interactions of these traits were clearly distinguished among the various P rates. However, aboveground trait expression registered increased growth from 6.0 to 10.0 ppm of P. The major root-attributed traits in 0.5 ppm of P are significantly increased vis-à-vis 10 ppm of P. Analysis of variance displayed a significant difference between the genotypes for PSTOL1 and PHT1 expression. In low P, maximum root length with a shoot and root dry weight was observed in a new indigenous accession, IC459373, with higher expression of PSTOL1 than in Dular and IR64-Pup1 in 0.5 ppm of P at 14 d. Among the 13 PHT1 genes, OsPT1, OsPT2, OsPT6, and OsPT13 showed significant upregulation in IC459373, Dular, and IR64-Pup1. These results indicated that studying the expression levels of the PSTOL1 and PHT1 gene family at the early growth stages would be helpful in identifying superior donors to improve low-P tolerance and P-use efficiency in rice breeding programs.